an ANALYSIS OF STUDENTS LEARNING STYLE IN ENGLISH CLASSROOM INTERACTION IN ELEVENTH GRADE STUDENTS AT SENIOR HIGH SCHOOL IN ACEH TIMUR - Nur Amalina (Journal of Education, Linguistics, Literature and Language Teaching, 2018)
This thesis analyze about the students learning style in English classroom interaction. Based on the study of senior high school, these students are hoped to know their tendency learning style and be able to apply appropriate learning strategies then the students will succeed in learning. Learning style is the process of teaching and learning in the classroom that focused on the student’s activity or characteristic in gathering information. The objectives of this study would to establish dominant kinds of student learning style in English classroom interaction and to find out the implementation of students learning style in English classroom interaction. This study uses qualitative descriptive method as research methodology to analysis and to find out the implementation toward students learning style English Classroom Interaction. The technique of collecting data is doing observation and questionnaire. The result of this study is to analyze the students learning style in English classroom interaction with six styles (visual, auditory, kinesthetic, tactile, group and individual) but in this class just have three styles. It can be proved by the answer of the questionnaire that they prefer to choose visual, kinesthetic, and group for their learning style. In this study, the writer expected that teacher can be able to understand the differences of their each student style.